A Systematic Review of the Impact of Invasive Alien Plants on Forest Regeneration in European Temperate Forests - Langmaier, Magdalena; Lapin, Katharina (Frontiers in Plant Science, 2020)
Invasive alien species (IAS) are one of the major threats to global and local biodiversity. In forest ecosystems, the threats caused by IAS include hybridization, transmission of diseases and species competition. This review sets out to analyse the impact of alien plant species on forest regeneration, which we consider to be one of the key stages in tree ecology for the survival of forest ecosystems in the future. The focus of the study is directly relevant to practitioners, forest managers and the conservation management of forests. With this systematic review, we aim to provide an overview of 48 research studies reporting on the impact and/or management of IAS in European temperate forests. We followed a multi-step protocol for compiling the publications for the literature review, with nine search queries producing a total of 3,825 hits. After several reduction rounds, we ended up with a grand total of 48 papers. We identified 53 vascular plant species having a negative influence on forest regeneration in Central European forests. In total, 21 tree species are reported to be impacted by IAS in 24 studies. The results of the review synthesis show that five impact mechanisms affect the regeneration success of native tree species: competition for resources, chemical impact on regeneration, physical impact on regeneration, structural impact on regeneration and indirect impact through interaction with other species. We identified in our synthesis management measures that have been recommended for application at different stages of biological invasions. The associated costs and required resources of management measures are under-reported or not accessible by reviewing the scientific literature. We can thus conclude that it is very import to improve the links between science and practical forest management. We expect that this review will provide direction for invasive plant species research and management aimed at protecting biodiversity in European temperate forest ecosystems.